Quasi-experimental impact estimates of immigrant labor supply shocks: The role of treatment and comparison group matching and relative skill composition - Abdurrahman Aydemir; Murat G. Kirdar (Institute for the Study of Labor (IZA), 2013)
This paper examines the employment effects of a large burst of immigration - the politically-driven exodus of ethnic Turks from Bulgaria into Turkey in 1989. In some locations, the rise in the labor force due to this inflow of repatriates was 5 to 10 percent. A key feature of our context is the strong involvement of the Turkish state in the settlement of earlier waves of repatriates, which provides us a strong source of exogenous variation in the 1989 immigrant shock across locations and brings our study closer to an ideal natural experiment. Using a reservoir of 342 cities and towns in Turkey with variable treatment intensity, this analysis places much attention on constructing a matched sample that is well balanced in terms of covariate distributions of the treatment and comparison groups - using propensity score matching. We find a positive effect of repatriates on the unemployment of non-repatriates. In fact, a 1 percent increase in the labor force due to repatriates increases the unemployment rate of natives by 0.4 percentage points. When the analysis is done according to skill groups, we find that the impact is the strongest on the young and on non-repatriates with similar educational attainment.
Keywords: J21; J61; 330; labor force and employment; immigrant workers; quasi experiments